Epileptic seizure first aid practices of publics in Northwest Ethiopia 2021: Unsafe practices of nearly three-fourths of the community - Asnakew, Sintayehu; Legas, Getasew; Belete, Amsalu; Beyene, Getnet Mihretie; Tedla, Assasahegn; Shiferaw, Kirubel; Mengist, Birhanu; Bayih, Wubet Alebachew; Feleke, Dejen Getaneh; Birhane, Binyam Minuye; Chanie, Ermias Sisay; Birhan, Zelalem; et al. (Frontiers in Neurology, 2022)
Background Religious and sociocultural beliefs influence how people with epilepsy (PWE) are treated and cared for. Many communities in Africa and other developing countries, including Ethiopia, believe that epilepsy is caused by evil spirits and should be treated with herbal plants by traditional doctors and religious leaders. The combination of these sociocultural beliefs and the level of community awareness of epilepsy affect first aid practices in the management of epileptic seizures. Objective This study aimed to assess epileptic seizure first aid practice of public and its associated factors in Northwest Ethiopia, south Gondar zone, Amhara, Ethiopia 2021. Methods A community-based cross-sectional study was conducted using a previously adapted standard questionnaire. A multistage cluster sampling technique was applied. A total of 756 participants were approached and 741 respondents completed the questionnaire with a response rate of 98.02%. Data were entered into Epi data version 4.4.2 and then exported to Statistical Package for Social Science (SPSS) version 24 for analysis. Descriptive and analytical statistical procedures and bivariable and multivariable binary logistic regressions with odds ratios and 95% confidence interval (CI) were employed. The level of significance of the association was determined at p < 0.05. Results Overall, 71.7% (95%CI: 68.3, 74.9) of the south Gondar community had unsafe practice measures in managing patients with seizure episodes. Individuals who were illiterate [adjusted odd ratio (AOR) = 1.99, 95%CI: 1.00.3.97] and participants who did not take training related to epilepsy (AOR = 2.07, 95%CI: 1.35, 3.17) and had poor knowledge about (AOR = 1.51, 95%CI: 1.06, 2.14) and a negative attitude toward epilepsy (AOR = 2.20, 95%CI: 1.50, 3.22) had unsafe practices compared to their counterparts. Conversely, participants who reached secondary education had safe practice measures (AOR = 0.4, 95%CI: 0.26, 0.63) in the management of epileptic seizures. Conclusions In this study, large numbers of the south Gondar community had unsafe practice measures in managing people with epileptic seizure episodes. Greater emphasis should be laid on individuals who were illiterate, in the provision of health education and/or training for the community to help them to acquire good knowledge about epilepsy and develop a positive attitude toward epilepsy.